Some new fixed point results in non-Archimedean fuzzy metric spaces - Salimi, Peyman; Vetro, Calogero; Vetro, Pasquale (Nonlinear Analysis: Modelling and Control, 2013)
In this paper, we introduce the notions of fuzzy (α,β,ϕ)-contractive mapping, fuzzy α-φ-ψ-contractive mapping and fuzzy α-β-contractive mapping and establish some results of fixed point for this class of mappings in the setting of non-Archimedean fuzzy metric spaces. The results presented in this paper generalize and extend some recent results in fuzzy metric spaces. Also, some examples are given to support the usability of our results.
Keywords: fuzzy metric spaces; non-Archimedean fuzzy metric spaces; fuzzy (α, β, ϕ)-contractive mappings; fuzzy α-φ-ψ-contractive mappings; fuzzy α-β-contractive mappings